An Appraisal of Teachers’ Professional Development in the Federal Capital Territory, Abuja-Nigeria - Abenu, Abigail; Yusufu, Funmilayo Alfa (Far Western Review, 2024)
This study assessed the professional development (PD) of primary and secondary school teachers in the Federal Capital Territory (FCT) Abuja, Nigeria. A mixed-method research design was adopted, where questionnaires and oral interviews were used to collect quantitative and qualitative data. A sample of 109 teachers from four purposively selected schools was used in the study. The findings revealed that a significant proportion of teachers (about 86%) have accessed PD; and about half,48.6%, of the teachers have benefited from government-sponsored professional development programmes between 2020- 2022. The appraisal of teachers’ work is not regular. While the perceptions of the impacts of PD were mixed, most of the teachers rated it as good and excellent. Factors inhibiting effective PD are diverse, the most important ones being inadequate funding, poorly organised PD and non-personalised PD for teachers’ needs and interests. It is rec commended that more funding should be channelled to PD; more personalised PD opportunities with input from teachers should be provided; as well as regular appraisals and the provision of feedback on teachers’ work.